Technology Integrated Teaching and Its Positive and Negative Impacts on Education - Turgay Küçük (International Journal of Social Sciences & Educational Studies, 2023)
Technology has become an integral component of the contemporary and educational world. This topic has been the subject of substantial research and several articles across the globe, but since such studies are limited in Iraq (approximately 10 articles, according to Google Scholar), it has been determined and researched. As a result, the positive and negative consequences of technology’s impact on education were studied in this study. A Google Form questionnaire with five questions was conducted to 26 volunteers with varying levels of education in order to assess the reception of the obtained data among educators. According to the collected data, ICT-integrated education has favorable effects on students and teachers and makes the acquired knowledge more permanent and credible.